Design Forecasting of Thermal Strength and Resource of Steam Turbine structural Components - Shulzhenko, N.G.; Gontarovskiy, P.P.; Garmash, N.G.; Melezhik, I.I. (Проблеми машинобудування, 2018)
The paper gives an overview of methodical and software as well as the results of the calculated research of the thermal strength, resource and crack resistance of steam turbine elements, which have been performed at A. Podgorny Institute of Mechanical Engineering Problems of the National Academy of Sciences of Ukraine during the last 15 years.